Psychological therapies and non-suicidal self-injury in LGBTIQ in accident and emergency departments in the UK: a scoping review. (19th May 2022) - Broadway-Horner, Matt; Kar, Anindya; Pemberton, Max; Ventriglio, Antonio
Abstract: Background: To identify psychological interventions that improve outcomes for those who overdose, especially amongst Lesbian, Gay, Bisexual, Transgender, Intersex and Questioning populations. Objective: To recognize and assess the results from all studies including randomized control trials (RCTs) that have studied the efficiency of psychiatric and psychological assessment of people who have depression that undergo non-suicidal self-injury (NSSI) by self-poisoning, presenting to UK Accident and Emergency Departments. Method: A scoping review of all studies including RCTs of psychiatric and psychological therapy treatments. Studies were selected according to types of engagement and intervention received. All studies including RCTs available in databases since 1998 in the Wiley version of the Cochrane controlled trials register in 1998 till 2021, Psych INFO, Medline, Google Scholar and from manually searching of journals were included. Studies that included information on repetition of the NSSI behaviour were also included. Altogether this amounts to 3900 randomized study participants with outcome data. Results: Seven trials reported repetition of NSSI as an outcome measure which were classified into four categories. Problem-solving therapy is indicated as a promising therapy and has shown to significantly reduce repetition in participants who NSSI by overdosing than patients in the control treatment groups consisting of standard after care. Conclusion: The data show that manualized cognitive therapy psychological intervention was more effective than TAU after care. However, these differences are not statistically significant with p = .15; CI 0.61, 1.0 which crosses the line of no effect. And psychodynamic interpersonal therapy is more effective than the standard treatment. Despite being only one study in this subgroup the analysis shows a statistical significance with p = .009, CI 0.08; 0.7.